Amniotic fluid neutrophils can phagocytize bacteria: A mechanism for microbial killing in the amniotic cavity. (13th July 2017) - Gomez‐Lopez, Nardhy; Romero, Roberto; Garcia‐Flores, Valeria; Xu, Yi; Leng, Yaozhu; Alhousseini, Ali; Hassan, Sonia S.; Panaitescu, Bogdan
Abstract : Problem: Neutrophils are capable of performing phagocytosis, a primary mechanism for microbial killing. Intra‐amniotic infection is characterized by an influx of neutrophils into the amniotic cavity. Herein, we investigated whether amniotic fluid neutrophils could phagocytize bacteria found in the amniotic cavity of women with intra‐amniotic infection. Methods: Amniotic fluid neutrophils from women with intra‐amniotic infection were visualized by transmission electron microscopy (n=6). The phagocytic activity of amniotic fluid neutrophils from women with intra‐amniotic infection and/or inflammation (n=10) or peripheral neutrophils from healthy individuals (controls, n=3) was tested using ex vivo phagocytosis assays coupled with live imaging. Phagocytosis by amniotic fluid neutrophils was also visualized by confocal microscopy (n=10) as well as scanning and transmission electron microscopy (n=5). Results: (i) Intra‐amniotic infection‐related bacteria including cocci (eg Streptococcus agalactiae ), bacilli (eg Bacteriodes fragilis and Prevotella spp.), and small bacteria without a cell wall (eg Ureaplasma urealyticum ) were found inside of amniotic fluid neutrophils; (ii) peripheral neutrophils (controls) rapidly phagocytized S. agalactiae, U. urealyticum, Gardnerella vaginalis, and Escherichia coli ; (iii) amniotic fluid neutrophils rapidly phagocytized S. agalactiae and G. vaginalis ; and (iv) amniotic fluid neutrophils slowly phagocytized U. urealyticum and E. coli ; yet, the process of phagocytosis of the genital mycoplasma was lengthier. Conclusion: Amniotic fluid neutrophils can phagocytize bacteria found in the amniotic cavity of women with intra‐amniotic infection, namely S. agalactiae, U. urealyticum, G. vaginalis, and E. coli . Yet, differences in the rapidity of phagocytosis were observed among the studied microorganisms. These findings provide a host defense mechanism whereby amniotic fluid neutrophils can kill microbes invading the amniotic cavity. Abstract : Amniotic fluid neutrophils can phagocytize bacteria, including Streptococcus agalactiae . (A) A scanning electron microscopy image of S. agalactiae . Magnification 10 000X. (B) A scanning electron microscopy image of amniotic fluid neutrophils and S. agalactiae (red arrow) prior to phagocytosis. Magnification 6000X. (C) Confocal microscopy images showing bacteria ingested by amniotic fluid neutrophils (white arrows). Separated images show DAPI staining in blue, CD15 (a neutrophil marker) in red, bacteria in green, and a merged image. Magnification 630X. (D) A transmission electron microscopy image of a neutrophil engulfing S. agalactiae . Magnification 2500X. Red arrows identify bacteria ingested by amniotic fluid neutrophils.